2020
DOI: 10.1183/23120541.00718-2020
|View full text |Cite
|
Sign up to set email alerts
|

COPD in the time of COVID-19: an analysis of acute exacerbations and reported behavioural changes in patients with COPD

Abstract: IntroductionThe impact of the SARS-CoV-2 pandemic, and lockdown measures, on acute exacerbations of COPD (AECOPD) is unknown. We aimed to evaluate the change in AECOPD treatment frequency during the first 6 weeks of lockdown in the UK compared with 2019 and assess changes in self-reported behaviour and well-being.MethodsIn this observational study in Leicestershire, UK, patients with COPD under a secondary care clinic were recruited. Exacerbation frequency in the first 6 weeks of COVID lockdown was compared wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 26 publications
5
70
0
1
Order By: Relevance
“…Deconditioning is a common cause of increased symptom burden in COPD and is likely a contributing factor in our cohort. Similar results were observed in a recent study by McAuley et al with an overall reduction in physical activity in COPD patients leading to general deconditioning [3]. A sedentary lifestyle is associated with worse outcomes including mortality in COPD patients and it is therefore essential that this trend is reversed as we recover from the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Deconditioning is a common cause of increased symptom burden in COPD and is likely a contributing factor in our cohort. Similar results were observed in a recent study by McAuley et al with an overall reduction in physical activity in COPD patients leading to general deconditioning [3]. A sedentary lifestyle is associated with worse outcomes including mortality in COPD patients and it is therefore essential that this trend is reversed as we recover from the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 87%
“…Asthma and Chronic Obstructive Pulmonary Disease (COPD) patients are considered at increased risk of dying from COVID-19 and were therefore subject to UK government shielding advice. While this may have protected against respiratory viruses; adverse effects, including reduced physical activity, social isolation, and increasing anxiety have been recognised consequences [3]. Airways disease management is multidisciplinary and there may also be pervasive deleterious effects due to suspension of clinical services including out-patient clinics, smoking cessation support, and pulmonary rehabilitation (PR) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The basic premise of our survey was that widespread, continued implementation of pandemic infection control measures was able to reduce the transmission of other viruses which in turn reduced exacerbations of airways diseases in both community and hospital settings [12][13][14][15][16][17][18][19][20] (noting that other circumstances of the pandemic such as cleaner air may also have contributed). Importantly, the pattern of residual disease severity does not support the counter-hypothesis that this reduction is due to patients avoiding healthcare during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic was associated with a dramatic fall in cases of influenza [11] and multiple studies have reported a substantial reduction in hospitalisations due to asthma and COPD exacerbations, temporally associated with the COVID-19 pandemic including introduction of respiratory virus infection control measures [12][13][14][15][16][17][18][19][20], likely because vulnerable people avoiding SARS-CoV-2 were also avoiding other respiratory viruses that are common causes of exacerbations [21].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a UK study using primary care prescription records as a proxy for exacerbation treatment courses reported a higher number of communitytreated exacerbations during the initial period of social restrictions compared with the same period in a previous year. 7 This was driven by an increased number of exacerbations in people having multiple events, rather than an increased proportion of people experiencing an exacerbation.…”
Section: Daryl O Cheng John R Hurstmentioning
confidence: 99%